Some suggestions for testing writing ability - Saludades, Jesusita C. 1938- ([Quezon City s.n.], 1965)
The author suggests ways of testing writing ability objectively. The suggestions are classified according to the elements of writing which are identified and discussed. Illustrations in the form of test items, mostly of the multiple choice type, are presented to show how these suggestions may be carried out.
Thesis (M.A.T.)--University of the Philippines
Keywords: Writing